Usefulness of ultrasound in the diagnosis of peritoneal tuberculosis - Sebastiana Atzori; Gianpaolo Vidili; Giuseppe Delitala (Journal of Infection in Developing Countries)
The peritoneum is one of the most common extrapulmonary sites of tuberculous infection. We report a case of peritoneal tuberculosis (TB) in a 25-year-old man. In this case, ultrasound of the abdomen played an important role in the diagnostic process. The diagnosis of this disease, however, remains a challenge because of its insidious nature, the variability of its presentation, and the limitations of available diagnostic tests. A high index of suspicion should be considered, particularly in high-risk patients with unexplained ascites. In our case ultrasound guided the diagnosis by rapidly identifying abnormal signs, which in high-prevalence settings are extremely suggestive of peritoneal tuberculosis.